STRUCTURALIST DEVELOPMENT MACROECONOMICS AND NEW DEVELOPMENTALISM: THEORETICAL FOUNDATIONS AND RECENT DEVELOPMENTS - Oreiro, José Luis; Silva, Kalinka Martins da (Práticas de Administração Pública, 2022)
The Brazilian New Developmentalist School, also known as "consensus of São Paulo", can be understood as an approach to the deep determinants of economic development in which macroeconomic policy regime has a key role in explaining the long-term growth differentials among countries, notably middle-income countries. The school was originated from the seminal works of Bresser-Pereira (2006, 2007 and 2009) who defined new developmentalism as a set of proposals for institutional reforms and economic policies, whereby the middle-income countries seek to achieve the per-capita income level of developed countries. The first aim of this article is to present the theoretical foundations and the recent developments of the New Developmentalism School. Regarding the theoretical foundations, New Developmentalism is based on the so-called Structuralist Development Macroeconomics, which can be understood as a synthesis between Classical Development Theory, Latin American Structuralism and Post-Keynesian demand-led growth models. One of the most known and controversial features of new developmentalism is the key role of the manufacturing industry and real exchange rate in the process of economic development. The present article presents the state-of-the art reasoning of the New-Developmentalist school about why and how real exchange rate and manufacturing industry matters for long-run growth. Finally, the article discusses the convergences and divergences between New-Developmentalism and Balance of Payments Constrained Growth models, which are up today the major heterodox explanation for uneven development.